(untitled) (Fiep Bulletin - online, 2012)
The ground fighting, as most of the Jiu-Jitsu, are sports that require high demand of physical, have characteristics acyclic, mesomorphic predominant components are subjected to high workloads and have marked the participation of lactic anaerobic metabolism . Athletes are exposed to strenuous effort during intermittent periods of activity and rest, resulting in the mobilization of large amounts of energy substrate in the absence or deficiency of oxygen, which favors the increase of blood lactate concentrations during fights. This study aimed to determine the acute physiological responses on the practice of Jiu-Jitsu, the assessment of cardiovascular parameters (heart rate and blood pressure), biochemical (lactate) and correlate them with aerobic fitness (VO2 max. and Threshold anaerobic) of young fans of the art. There was a gradual increase in cardiac stress every minute of the fight, having been found near the maximum heart rate due to some athletes. Systolic blood pressure also showed the high end of the match (1 min recovery), but with significant decline in the following periods of rest, thus indicating post-exercise hypotensive effect. The athletes had higher values ??of VO2 max and VO2 at anaerobic threshold were those who showed better tolerance to treadmill running test, and developed faster recovery of blood lactate. Thus, this study reinforces the notion that better known aerobic fitness results in physiological responses favorable to good athletic performance, even in predominantly anaerobic modalities, such as Jiu-Jitsu.